A COMPARATIVE STUDY OF A NEW JUNIOR GUIDE CAMP MODEL FOR DEVELOPING 9TH GRADE STUDENTS’ ENGLISH-SPEAKING SKILLS - Prachumchai, Sapolachet; Yokanya, Nikom Yokanya; Sriraungrith, Preecha; Tao-ngoen, Samran (Journal of MCU Phetchaburi Review, 2023)
The current research and development study on teaching innovations aims to compare the English language performance of 9th grade students using a diminutive guide camp between groups of students. In the first semester of the 2022 school year, 36 ninth grade students at Niyomsilpanusorn School in Wichian Buri District, Phetchabun Province, Thailand, participated in this study. The study used a targeted sampling technique, and because the English major underperformed in the previous semester, the 36 participants were divided into experimental and control groups. Among the research tools were a tour guide language exam and a diminutive guide camp teaching pack. Independent sample t-tests were used to analyze the data. Finally, the comparison of the English learning outcomes between the experimental and control groups was statistically significant at the 0.05 level.